Assessment of global longitudinal strain using standardized myocardial deformation imaging: a modality independent software approach - Riffel, Johannes; Keller, Marius; Aurich, Matthias; Sander, Yannick; André, Florian; Giusca, Sorin; Siepen, Fabian aus dem; Seitz, Sebastian; Galuschky, Christian; Korosoglou, Grigorios; Mereles, Derliz; Katus, Hugo; et al. (Clinical research in cardiology, 2015)
Myocardial deformation measurement is superior to left ventricular ejection fraction in identifying early changes in myocardial contractility and prediction of cardiovascular outcome. The lack of standardization hinders its clinical implementation. The aim of the study is to investigate a novel standardized deformation imaging approach based on the feature tracking algorithm for the assessment of global longitudinal (GLS) and global circumferential strain (GCS) in echocardiography and cardiac magnetic resonance imaging (CMR).
Gesehen am 18.06.2020